Transformasi Kepemimpinan Digital di Dunia Pendidikan: Analisis Faktor-Faktor Multiplikasi - Jeconiah Sugiyanto; Yenny Luisa Manongga; Sie Ngoh; Landong Siringo; Manlian Ronald Adventus (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
The transformation of digital leadership in education has become an urgent necessity amid rapid technological advancements and shifting social paradigms. This study aims to identify multiplying factors in digital leadership, examine strategies for accelerating transformation, and integrate Biblical leadership values within the digital context. Using a qualitative-descriptive approach through literature review, the paper finds that transformational leadership styles, distributed leadership, human resource digital competencies, innovation culture, technological infrastructure, and data-driven decision-making play crucial roles in enhancing digital leadership transformation. Moreover, values such as humility, wisdom, integrity, and love, as taught in the Bible, provide a strong moral foundation for leadership in the digital era. The study recommends capacity building for leaders, the development of learning communities, supportive policies, and the integration of ethical-spiritual values as key drivers for successful leadership transformation in education.